Eupafolin ameliorates COX-2 expression and PGE2 production in particulate pollutants-exposed human keratinocytes through ROS/MAPKs pathways. (2nd August 2016) - Lee, Chiang-Wen; Lin, Zih-Chan; Hsu, Lee-Fen; Fang, Jia-You; Chiang, Yao-Chang; Tsai, Ming-Horng; Lee, Ming-Hsueh; Li, Shu-Yu; Hu, Stephen Chu-Sung; Lee, I-Ta; Yen, Feng-Lin
Abstract: Ethnopharmacological relevance: Eupafolin is a major bioactive compound derived from the methanolic extract of the medicinal herb Phyla nodiflora, which has been used in traditional Chinese medicine to treat various inflammatory diseases. Recently, particulate air pollutants have been shown to induce inflammation of the skin. In this study, we seek to determine whether eupafolin can inhibit the production of inflammatory mediators in a human skin keratinocyte cell line exposed to particulate air pollutants (particulate matter, PM), and determine the molecular mechanisms involved. Materials and methods: Human keratinocyte HaCaT cells were treated with PM in the presence or absence of eupafolin. Cyclooxygenase-2 (COX-2) protein and gene expression levels were determined by Western blotting, RT-PCR and luciferase activity assay. Prostaglandin E2 (PGE2 ) production was evaluated by the enzyme immunoassay method. Generation of intracellular reactive oxygen species (ROS) was measured by the dichlorofluorescin (DCFH) oxidation assay, and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity was determined by a chemiluminescence assay. For in vivo studies, COX-2 expression in the skin of BALB/c nude mice was analyzed by immunohistochemistry. Results: Eupafolin inhibited PM-induced COX-2 protein and gene expression and PGE2 production in HaCaT cells. In addition, eupafolin suppressed PM-induced intracellular ROS generation, NADPH oxidase activity, MAPK (ERK, JNK and p38) activation and NK-κB activation. In vivo studies showed that topical treatment with eupafolin inhibited COX-2 expression in the epidermal keratinocytes of PM-treated mice. Conclusions: Eupafolin exerts anti-inflammatory and antioxidant effects on skin keratinocytes exposed to particulate air pollutants, and may have potential use in the treatment or prevention of air pollutant-induced inflammatory skin diseases in the future. Graphical abstract: